IEO Annual Report 2012. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2012)
This Independent Evaluation Office (IEO) Annual Report 2012 presents an overview of overall developments in FY2012. In FY2012, the IEO expended approximately 97 percent of its total budgetary resources, including the approved budget amount and the resources carried forward from FY2011 as authorized. Vacancies amounted to about one and one-half staff years over the course of the financial year. This level of vacancies is within the range of what could be expected in a small organization with structural difficulties in recruitment and retention.